The Campus Canopy, 1940-05-03 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, May 3, 1940. Vol. 6, No. 22. -- Special May Day Issue -- Schedule Of May Day Events -- Parham And Williams, New S.G.A. Officers, Installed -- Bell Will Crown Garbutt Queen Of May; “Sleeping Beauty” Is Theme Of Festivity -- Dedication Of Library Will Be In June
Digitized from original print, Valdosta State University Archives and Special Collections, January 11, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; Valdosta State College; Valdosta State University; GSWC; VSC; VSU; 1940s; 1940; May Day